Axial loading mechanism analyses and evaluation methods of CCFT short columns with gap defects. (December 2022) - Shen, Qihan; Wang, Jingfeng; Wang, Fengqin; Li, Guoqiang; Hu, Ziming
Abstract: The gap defect has proved to be a common quality issue in concrete-filled tubular (CFT) structures, which offers distinct unfavourable effects on their mechanics properties. To determine out the guidelines of gap defect affecting the axial loading performance of circular CFT (CCFT) short columns, this paper develops an array of refined numerical models of the axially-compressed CCFT short columns with spherical-cap gaps (CCFT-SG) and circumferential gaps (CCFT-CG), whose accuracy is verified by existing experiments. The typical axial force versus longitudinal displacement ( N - Δ ) curves, the contact stress, the longitudinal stress distribution and the failure modes are respectively given focus to reveal the intrinsic axial loading mechanism of the CCFT short columns, taking the existence of the gap defect into consideration. Based on these analyses, various design methods using confinement regionalization and circumferential expansion thoughts are proposed and adopted to evaluate the load bearing capacities of the axially-compressed CCFT-SG and CCFT-CG short columns. The results declare that the appearance of the gap defects dramatically weakens or delays the contact behaviour between the infilled concrete and the hollow tube, which accelerates the local bulging of the tube, reduces the longitudinal stress of the core concrete, and therefore the axial resistance of the CCFT short column is distinctly influenced. The design approaches delivered in this paper can assess the axial resistances of the CCFT short columns with gap defects accurately according to the test validation. The research may provide a theoretical basis and a reliable way for evaluating and treating the actual CFT structures with gap defects.